2015
DOI: 10.1007/s13277-015-3416-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical evidence of miR-494 and PTEN in non-small cell lung cancer

Abstract: The aim of this study was to explore the expression and clinical significance of miR-494 and PTEN (phosphatase and tensin homologue deleted on chromosome ten) in non-small cell lung cancer (NSCLC). Immunohistochemistry for PTEN and in situ hybridization (ISH) for miR-494 were performed in 92 NSCLC tissues and 10 normal lung tissues to detect their expression, and correlation between their expression with clinical characteristics and prognosis was analyzed. The expression of miR-494 was significantly higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 22 publications
1
33
2
1
Order By: Relevance
“…The expression of miR-494 was negatively associated with the grade of differentiation. In addition, patients with upregulation of miR-494 had a shorter overall survival rate (24). Overexpression of miR-494 improved angiogenesis in NSCLC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The expression of miR-494 was negatively associated with the grade of differentiation. In addition, patients with upregulation of miR-494 had a shorter overall survival rate (24). Overexpression of miR-494 improved angiogenesis in NSCLC.…”
Section: Discussionmentioning
confidence: 94%
“…It has been demonstrated that the expression of miR-494 is altered in several types of human cancer; it is upregulated in the cancer tissues of hepatocellular carcinoma (22), colorectal (23) and non-small-cell lung cancer (24), while it is downregulated in various types of human cancer, including gastric carcinoma (25), prostate cancer (26), esophageal squamous cell carcinoma (ESCC) (27), oral cancer (28), breast cancer (29), pancreatic cancer (30), chondrosarcoma (31) and cervical cancer (32). These conflicting studies indicate that the expression of miR-494 in cancers has tissue specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our finding of it being suppressed in BCC relative to SCC and HK, miR-494 is induced in several cancers (malignant breast cancer, esophageal squamous cell carcinoma, gastric carcinoma, oral cancer, ovarian cancer and pancreatic cancer) (148)(149)(150)(151)(152)(153)(154)(155)(156)(157). Rather than inferring its suppression in BCC, perhaps it is induced early in the transformation of keratinocytes to SCC.…”
Section: A Study Population Demographics and Histopathological Analysiscontrasting
confidence: 99%
“…On the other hand, a previous study has failed to find association between the mRNA expression level of mTOR gene and pathologic type [16]. Similarly, another study showed that the mRNA expression of the mTOR gene tended to increase in patients with advanced stage (stage III) NSCLC, however, this elevation did not reach statistical significance (9).…”
Section: Discussionmentioning
confidence: 90%
“…With regard to mTOR expression, it was reported that there was an up-regulation in the expression level of mTOR in tumor tissue as compared to adjacent-tumor tissue [15]. Similarly, Wang et al showed that mRNA expression levels of mTOR in the tumor tissue were outstandingly higher than in adjacent-tumor tissue [16]. Moreover, Liu et al reported that mTOR mRNA expression was elevated in tumor tissue as compared to matched normal tissue [9].…”
Section: Discussionmentioning
confidence: 99%